Socialization of health: An undeniable necessity for the formation of responsible medical universities in Iran - Siavash Moradi (Shahid Beheshti University of Medical Sciences, 2017)
The World Health Organization introduced social responsibility for the medical universities centered on education, research and provision of services. This definition states that social responsibility is "obligation of the medical schools to direct their education, research and service activities towards addressing the priority health concerns of the community, region, and/or nation they have a mandate to serve, The priority health concerns are to be identified jointly by governments, health care organizations, health professionals and the public"(1). Using the above definition as a model, Iran's medical universities were expected to think about socialization of health much earlier than what actually recently happened. However, what has occurred in relation to community-oriented medicine in Iran over the last quarter century has mainly been focused on increasing community access to specialized medical services and hasty implementation of the family physician program in rural areas and some cities. Clearly, socialization of health is not possible with merely setting up a social deputy in the body of the Ministry of Health and Medical Education. Socialization of health means communal involvement in maintaining and promoting individual, social, and psychological health of the community, and this will only be achieved through community-based medical education that not only trains skilled and competent human resources, but also focuses on empowerment of the community, or in another sense, promotion of community health. In other words, it is necessary to consider social responsibility as a principle in the excellence of medical education (2). Indeed what percentage of Iranians actually take part in decision-making about health? What percentage of the general public in Iran are addressed by articles published by medical universities' experts? To what extent contents of the medical universities' portals cover requirements of the general community? What is universities' approach to community empowerment? Moreover, the bigger question is whether Iranians know what their own health requirements are. As much as a responsible medical university is concerned about professional competence and professionalism of its graduates, it should look at improving health literacy of the community it covers. Such a university does not confine education to the enclosure of the university, but addresses education of the community at three levels: Generic, Targeted, and Tailored. Graduates from a responsible university know that community health can be ensured only by increasing health literacy of the community, and even their participation in the field of health research known as community-based participatory research. Although increasing access of different strata of the community to health services and providing the highest quality of services are worthwhile per se; these are not sufficient for community to encounter and cope with health-threatening factors. A responsible university responds to the ever-changing community needs, and to this end, takes advantage of a surveillance system that is able to quickly identify new community needs and finding support to resolve these needs (3). A responsible university collaborates with other organizations and institutions, general community, other professional groups, policy-makers and even statesmen, and that is how it can conduce the system of continuous provision of health services (3). In addition, a medical university formed on the bases of social responsibility will undoubtedly put health promotion and diseases prevention on top of its agenda (4). The fact that despite quantitative progress of medical universities in recent decades, some simplest health hazards are still not easily prevented, this means that responsiveness and accountability are neglected by most Iran's medical universities. Although in recent years, indicators of social responsibility of medical universities have been defined (5), and even highlighted in the last transformation of Iran's medical education, there seems to be a long way to achieving the ultimate goal of social accountability.